Shadows of Swanford Abbey - Klassen, Julie, 1964- (Minneapolis, Minnesota : Bethany House Publishers, a division of Baker Publishing Group, 2021)
"In pursuit of an author who could help get her brother published, Rebecca Lane stays at Swanford Abbey, a grand hotel rumored to be haunted. It is there she encounters Sir Frederick-the man who broke her heart. When a mysterious death occurs, Rebecca is one of the suspects, and Fredrick is torn between his feelings for her and his search for the truth"--
Keywords: Brothers and sisters -- Fiction; Haunted places -- Fiction; Authors -- Fiction; Murder -- Fiction -- Investigation; Man-woman relationships -- Fiction; England -- Fiction; Christian fiction; Romance fiction; Detective and mystery fiction